2009
DOI: 10.1016/s0025-6196(11)60751-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Dependency and the Physician

Abstract: Although the nature and scope of addictive disease are commonly reported in the lay press, the problem of physician addiction has largely escaped the public's attention. This is not due to physician immunity from the problem, because physicians have been shown to have addiction at a rate similar to or higher than that of the general population. Additionally, physicians' addictive disease (when compared with the general public) is typically advanced before identification and intervention. This delay in diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…6,13,16 Mayo Clinic is no exception in this regard; thus, it is not surprising that concerted efforts to detect drug diversion began in the Department of Anesthesiology. Detection has often been precipitated by personnel underperformance or behavioral changes at work, frequent unexplained work absences, patients who seem to be undermedicated in the period after surgery despite documentation of administration of seemingly adequate narcotic dosages, and, rarely, HCW death related to a CS.…”
Section: Department Of Anesthesiologymentioning
confidence: 99%
“…6,13,16 Mayo Clinic is no exception in this regard; thus, it is not surprising that concerted efforts to detect drug diversion began in the Department of Anesthesiology. Detection has often been precipitated by personnel underperformance or behavioral changes at work, frequent unexplained work absences, patients who seem to be undermedicated in the period after surgery despite documentation of administration of seemingly adequate narcotic dosages, and, rarely, HCW death related to a CS.…”
Section: Department Of Anesthesiologymentioning
confidence: 99%
“…Previous literature suggests that up to 12% of physicians will suffer from substance abuse during their career. 2,3 Abuse patterns, however, are not distributed evenly across specialties. Surveys conducted from the early 1980s-2008 suggest that anesthesiologists may be at highest risk, particularly during the earlier stages of their career.…”
Section: Résumémentioning
confidence: 99%
“…10 Such high success rates among HCPs are related to multiple factors, including the individual's motivation to maintain licensure and professional practice, the extensive treatment provided to this group, and the long-term monitoring established by state PHPs. 11 In fact, one can clearly make the argument that reported success rates are so high that introducing opioid maintenance to this paradigm would not be appropriate. Individual and large collaborative studies of state PHPs have demonstrated that under ideal circumstances, 80% of physicians being monitored for the 5 years after abstinence-based, 12-step treatment do not have a single relapse.…”
Section: W E Congratulate Mayo Clinic Proceedings and The Authors Hammentioning
confidence: 99%